2007
DOI: 10.1097/ta.0b013e318047983d
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction in Trauma: Even a Little Costs a Lot

Abstract: Vigilance in preventing creatinine increases and ameliorating or removing potential causes should occur as soon as creatinine begins to rise to avoid worsening renal function, to reduce cost, and to improve patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 7 publications
6
31
1
Order By: Relevance
“…[2,3,7,[38][39][40] However, few have focused on describing the mortality associated with AKI in trauma. [21,25,27] Our data further strengthen the findings of prior investigations by showing that early AKI is associated with higher crude and adjusted mortality in ICU patients with trauma. [21,25,27] In the only other study to evaluate early AKI in trauma, Ala-Kokko et al showed that "renal failure" defined by SOFA score >2 had an adjusted OR of 8.2 for hospital mortality.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…[2,3,7,[38][39][40] However, few have focused on describing the mortality associated with AKI in trauma. [21,25,27] Our data further strengthen the findings of prior investigations by showing that early AKI is associated with higher crude and adjusted mortality in ICU patients with trauma. [21,25,27] In the only other study to evaluate early AKI in trauma, Ala-Kokko et al showed that "renal failure" defined by SOFA score >2 had an adjusted OR of 8.2 for hospital mortality.…”
Section: Discussionsupporting
confidence: 79%
“…Brandt et al found that "renal failure" occurred in 23.8% of patients when defined by an absolute serum creatinine >133μmol/L or a relative changes of >50% or >44 μmol/L. [21] While similar to our incidence estimate, this study was performed at a single level I trauma center and thus potentially prone to selection bias. Recently, the RIFLE criteria were applied in a single-center study of 304 critically ill burn patients (>10% total-body surface area).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations